Online networks and subjective well-being - Fabio Sabatini; Francesco Sarracino (Economics and Econometrics Research Institute (EERI), 2014)
Does Facebook make people lonely and unhappy? Empirical studies have produced conflicting results about the effect of social networking sites (SNS) use on individual welfare. We use a representative sample of the Italian population to investigate how actual and virtual networks of social relationships influence subjective well-being (SWB). We find a significantly negative correlation between online networking and self-reported happiness. We address endogeneity in online networking by exploiting technological characteristics of the pre-existing voice telecommunication infrastructures that exogenously determined the availability of broadband for high-speed Internet. We try to further disentangle the direct effect of SNS use on well-being from the indirect effect possibly caused by the impact of SNS's on trust and sociability in a SEM analysis. We find that online networking plays a positive role in SWB through its impact on physical interactions. On the other hand, SNS use is associated with lower social trust, which is in turn positively correlated with SWB. The overall effect of networking on individual welfare is significantly negative.
Keywords: C36; D85; O33; Z13; 330; Social participation; online networks; Facebook; social trust; social capital; subjective well-being; hate speech; broadband; digital divide